Antibacterial Activity of Some Substituted (1,4)-Benzothiazino-(2,3-b)-phenothiazines - Ojha, K.G.; Tahiliani, Heer (Asian Journal of Chemistry, 2010)
The title compounds [1, 4-benzothiazino-(2,3-b)-phenothiazines] were synthesised by condensing 2-aminothiophenols with halogeno-p- benzoquinones in presence of anhydrous sodium acetate. The compounds were screened for their antibacterial activity against Pseudomonas solanaceacum, Pseudomonas syringae and Pseudomonas viridiflalva. Some of these compounds show significant antibacterial activity.